Implications of Prenatal Gentle Yoga on Low Back Pain among Women in the Second and Third Trimesters of Pregnancy - Indriyani Makmun; Ana Pujianti Harahap; Aulia Amini; Rizkia Amilia; Ni Wayan Ari Adiputri (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Back pain during pregnancy is caused by changes in anatomical and hormonal structures. Anatomical changes occur because the role of the spine which is getting heavier to balance the body due to the enlargement of the uterus and fetus. Another cause is an increase in the relaxin hormone which causes the spinal ligaments to be unstable so that it is easy to clamp blood vessels and nerve fibers. This study was conducted by applying prenatal gentle yoga. Yoga movements were carried out for 60 minutes so as to reduce low back pain that is often experienced by pregnant women in the II and III trimesters. This was a Quasi-Experimental study with one group non-equivalent pre-test post-test design. The study samples of 30 women in the II and III trimesters of pregnancy who experienced back pain were selected through total sampling technique. The study was conducted from March to May 2022. The results of the study showed that there was a difference in the mean value before and after being given prenatal gentle yoga intervention in reducing low back pain among women in the II and III trimesters of pregnancy, with a p-value of 0.000<0.005. It is recommended that prenatal gentle yoga can be implemented among pregnant women since yoga movements can help pregnant women in managing breathing, preparing for the delivery process and can reduce the symptoms of complaints that are often experienced by pregnant women.